In vivo imaging of the spatial heterogeneity of intratumoral acidosis (pH) as a marker of the metastatic phenotype in breast cancer - Alessia Corrado; Nicla Lorito; Annasofia Anemone; Antonella Carella; Daisy Villano; Elisa Pirotta; Francesco Gammaraccio; Angela Subbiani; Marina Bacci; Walter Dastrù; Andrea Morandi; Dario Livio Longo (Breast Cancer Research)
Abstract Background Metabolic alterations, including acidosis in the tumor microenvironment, have been extensively linked to more aggressive phenotypes and increased therapy resistance. However, current imaging techniques are limited in their ability to capture extracellular tumor acidosis precisely and assess spatial heterogeneity in vivo, making its association with augmented malignancy poorly understood. In this study, we investigated whether Magnetic Resonance Imaging– Chemical Exchange Saturation Transfer (MRI-CEST) technique for tumor pH imaging of intratumoral acidosis could differentiate between metastatic and non-metastatic breast cancers. Methods Isogenic metastatic (4T1) and non-metastatic (67NR) breast cancer cell lines were characterized for their metabolic and acidosis features, including LDH-A/PDK-1 expression, glucose consumption, extracellular acidification rate (ECAR) and oxygen consumption rate (OCR). Potential relationship between tumor acidosis, vascularization and hypoxia with metastatic potential was assessed in vivo by MRI-based imaging approaches in orthotopic breast tumors. Validation of MRI findings was assessed ex vivo by western blot, immunohistochemistry and immunofluorescence assays for a multiparametric characterization of tumor microenvironment and metabolic properties. Results We observed a higher energetic profile of the 4T1 cells compared to the 67NR cells, alongside elevated glycolytic (LDH-A, PDK-1), hypoxia (CAIX, Pimonidazole), and vascularization (CD31) markers in 4T1 orthotopic primary tumors, which were associated with a greater metastatic propensity. MRI-CEST tumor pH imaging revealed increased extracellular tumor acidity in 4T1 tumors, along with marked spatial intratumoral heterogeneity, in contrast to the more homogenous 67NR tumors, as further confirmed by LAMP-2 staining. Notably, this spatial intratumor heterogeneity in acidosis enables clear differentiation between high- and low-malignancy tumors. Conclusions These findings underscore the role of tumor acidosis and its spatial heterogeneity in promoting aggressive phenotypes and highlight the potential of in vivo tumor pH imaging as a marker of malignancy in breast cancers.